Do age and work pace affect variability when performing a repetitive light assembly task?. (January 2022) - Gilles, Martine A.; Gaudez, Clarisse; Savin, Jonathan; Remy, Aurélie; Remy, Olivier; Wild, Pascal
Abstract: This study examined whether a repetitive light assembly task could be performed according to different movement sequences identified as ways of doing (WoD), and whether the age of the participants or the work pace affected the number of WoDs selected by each participant, or the kinematic parameters for each WoDs. For two work paces, 62 right-handed men in 3 age-groups were asked to fix a handle on a base with 2 nuts without discontinuity for a period of 20 min; no assembly procedure was demonstrated. The WoDs were characterized by a cross tabulation video coding method, and by measuring vertical force applied and the parameters of upper limb kinematics, as well as these measures' approximate entropy (ApEN). Five main different WoDs were used. Although most participants varied their WoD, neither participant age nor work pace affected the number of WoD they used. However, the WoDs differed from each other by the sequence of movements and by the level of ApEn of their kinematic variables without interfering with the production rate. Allowing operators to vary their WoDs when performing repetitive tasks could reduce strain on the locomotor system. Highlights: Performing an assembly was considered as several associated and organised movements corresponding to a way of doing (WoD). Participant's age or pace of work had no impact on the number of WoDs they selected. Five main WoD were observed to be used to perform the same repetitive light assembly task. Movement variability constituting WoDs was not influenced by operator age or pace of work. The most common WoD used presented a majority of low-complexity kinematic and force signals and the shortest cycle time.